Medical history of thyroid cancer does not impair prognosis in non-metastatic breast cancer patients: an analysis study based on SEER database and external cohort - Li, Shuai; Chen, Xiaosong; Shen, Kunwei (Frontiers in Oncology, 2024)
BackgroundNon-metastatic breast cancer patients who had a medical history of skin or cervix cancers were presently eligible for clinical trials while few data were available regarding thyroid gland cancer. The study estimated the rate of prior thyroid gland cancer and evaluated its impact on survivals among breast cancer patients.MethodsNon-metastatic invasive breast cancer patients from the SEER database (SEER cohort) between 2010 and 2019 and Ruijin Hospital (Ruijin cohort) during 2009 and 2019 were retrospectively analyzed. Ascian or Pacific Island patients in the SEER cohort (SEER API cohort) were analyzed separately. Chi-square test and multivariate logistic regression analysis were performed to describe the clinical features. Kaplan-Meier analysis and Cox proportional hazards model were used to compare the overall survival (OS) and breast cancer specific survival (BCSS).ResultsA total of 136,441 patients from the SEER cohort, 17,183 from the SEER API cohort, and 8,079 from the Ruijin cohort were enrolled, of whom 0.68%, 0.81%, and 1.06% had a medical history of thyroid gland cancer, respectively. Patients with prior thyroid gland cancers were significantly older (51-60 years: OR 1.84, 95% CI 1.46-2.30, P < 0.001; 61-70 years: OR 2.00, 95% CI 1.61-2.50, P < 0.001; > 70 years: OR 1.51, 95% CI 1.18-1.92, P = 0.001) and more likely to be API (OR 1.23, 95% CI 1.03-1.48, P = 0.026) versus other races. Multivariate analysis demonstrated that patients with a history of thyroid gland cancer had comparable OS (SEER: HR 0.87, 95% CI 0.68-1.11, P = 0.257; SEER API: HR 0.53, 95% CI 0.22-1.28, P = 0.159; Ruijin: HR 1.07, 95% CI 0.26-4.29, P = 0.811) and BCSS (SEER: HR 0.72, 95% CI 0.49-1.08, P = 0.117; SEER API: HR ∞, 95% CI ∞-∞, P = 0.878; Ruijin: HR 0.70, 95% CI 0.10-4.98, P = 0.750) versus those without primary malignancies in the three cohorts.ConclusionThere were of a sizable of non-metastatic breast cancer patients with medical history of thyroid gland cancer, which was related with different races. Prior thyroid gland cancer had no adverse impact on clinical outcomes, indicating possible eligible in further clinical trials.